2008
DOI: 10.1016/j.mod.2007.10.008
|View full text |Cite
|
Sign up to set email alerts
|

pannier encodes two structurally related isoforms that are differentially expressed during Drosophila development and display distinct functions during thorax patterning

Abstract: Previous studies have shown that the pannier (pnr) gene of Drosophila encodes a GATA transcription factor which is involved in various biological processes, including heart development, dorsal closure during embryogenesis as well as neurogenesis and regulation of wingless (wg) expression during imaginal development. We demonstrate here that pnr encodes two highly related isoforms that share functional domains but are differentially expressed during development. Moreover, we describe two genomic regions of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
73
0
2

Year Published

2009
2009
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(80 citation statements)
references
References 45 publications
(58 reference statements)
5
73
0
2
Order By: Relevance
“…See supplementary material Table S1 for primer sequences. Note that Pnr exists in two isoforms (Fromental-Ramain et al, 2008), with conserved Sgg phosphorylation sites: in this work, the pnrb isoform was used.…”
Section: Site-directed Mutagenesis and Generation Of Transgenic Fliesmentioning
confidence: 99%
See 1 more Smart Citation
“…See supplementary material Table S1 for primer sequences. Note that Pnr exists in two isoforms (Fromental-Ramain et al, 2008), with conserved Sgg phosphorylation sites: in this work, the pnrb isoform was used.…”
Section: Site-directed Mutagenesis and Generation Of Transgenic Fliesmentioning
confidence: 99%
“…Interestingly it has been shown that the Drosophila transcription factor Mad is also a target of Sgg and that phosphorylation-resistant Mad proteins are hyperactive (Eivers et al, 2009). Mad is activated by Dpp/TGFb signalling, which in turn regulates expression of both pnr and the Iro-C genes in the thorax (Sato and Saigo, 2000;Tomoyasu et al, 2000;Shi and Massague, 2003;Letizia et al, 2007;Fromental-Ramain et al, 2008) (Fig. 5).…”
Section: Research Articlementioning
confidence: 99%
“…Генная сеть Neurogenesis:Prepattern руют транскрипцию u-shaped (Hannon et al, 1991;Tsai et al, 1991;Ramain et al, 1993;Cubadda et al, 1997;Haenlin et al, 1997;Fromental-Ramain et al, 2008. На третьем уровне управления сосредоточены эле-мен ты контроля за функционированием основного клю-чевого объекта сети с максимальной связностью -про-нейральных генов комплекса achaete-scute.…”
Section: системная биология и моделированиеunclassified
“…Наработка Wg приводит к активации sgg, а киназа Sgg фосфорилирует Pnrβ, преобразуя его в неак-тивную форму. Таким образом, превышение содержания Pnrα над содержанием Pnrβ в клетках имагинального диска закрывает для них нейральный путь дифференцировки, полностью исключая возможность активации генов AS-C. Этот контур функционирует в пределах презумптивного нотума и обеспечивает уточнение взаимного распо-ложения пронейральных кластеров (Sato, Saigo, 2000;Fromental-Ramain et al, 2008Yang et al, 2012).…”
Section: системная биология и моделированиеunclassified
“…The Drosophila model allowed the extensive genetic screening and functional analysis of Tinman (NKX2. 5 Yin et al, 1997;Akasaka et al, 2006;Zaffran et al, 2006;Qian et al, 2011;Ryu et al, 2011), Hand (dHAND, eHAND, Han andOlson, 2005; www.intechopen.com Lo et al, 2007), tailup/isl-1 (Islet, Tao et al, 2007;Mann et al, 2009), Pannier (GATA4, Alvarez et al, 2003Fromental-Ramain et al, 2008;Qian et al, 2008;Qian and Bodmer, 2009), Neuromancer-1/-2 (TBX20, Miskolczi-McCallum et al, 2005;Qian et al, 2005a;Leal et al, 2009), and Dorsocross-1/-2/-3 (TBX5, and revealed a conserved cardiac transcription factor network responsible for heart specification (Olson, 2006). Drosophila and vertebrates also share the same inductive and instructive signaling pathways (Wnt, FGF, BMPs, for review see Frasch, 1999;Cripps and Olson, 2002) during early heart development.…”
Section: Comparison Between Drosophila and Vertebrate Cardiogenesismentioning
confidence: 99%